Cover Image. (22nd December 2020) - Yoon, Young Jun; Lee, Jae Sang; Kang, In Man; Lee, Jung‐Hee; Kim, Dong‐Seok
Abstract : The cover image is based on the Special Issue Research Article Design and Optimization of GaN-based Betavoltaic Cell for Enhanced Output Power Density by Young Jun Yoon et al., https://doi.org/10.1002/er.5909 .